1998
DOI: 10.1159/000015822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Three Strategies of Verbal Scoring of the Glasgow Coma Scale in Patients with Stroke

Abstract: Presence of aphasia in patients with stroke poses a problem in the use of the full form (eye-motor-verbal) Glasgow Coma Scale (GCS). Stroke investigators and clinicians have used three different strategies to deal with the untestable verbal subscale, i.e. eliminating the verbal subscale; pseudoscoring with ‘one’, and median value substitution; but the predictive accuracy of the strategies has not been compared. To compare the predictive accuracy of the three strategies for acute mortality in stroke, we prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In contrast to other studies we had a strict methodology for solving this problem scoring for 1 in intubated patients. This is also the method favored by Prasad et al [14]. They found that the verbal score can be omitted in stroke patients with a good prediction of 2-week mortality.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to other studies we had a strict methodology for solving this problem scoring for 1 in intubated patients. This is also the method favored by Prasad et al [14]. They found that the verbal score can be omitted in stroke patients with a good prediction of 2-week mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Some investigators have modified the GCS by imputing a verbal score to intubated patients. 42–44 To determine whether an imputed verbal sub-score changed our main findings we performed a sensitivity analysis in which we imputed the verbal sub-score for both intubated patients and, separately, for all patients, using the methodology of Meredith et al 43 …”
Section: Methodsmentioning
confidence: 99%
“…The NIH stroke scale broadly defines consciousness as alert, not alert with or without ‘stimulation’, and coma, and subsequently evaluates comprehension and the response to 2 questions. The GCS is the most widely used coma scale, but the verbal component in particular becomes much less reliable in patients with stroke due to dysphasia and dysarthria or is impossible to assess in intubated patients [4,5,6]. Clearly, there is a need for a more comprehensive coma scale that could be useful in evaluating stroke patients, but prior attempts to modify or replace the GCS have not been successful [7,8,9].…”
Section: Introductionmentioning
confidence: 99%